Investigation into factors inhibiting effective job performance of academic librarians at selected university libraries in North central Nigeria (2020)
The article examined factors that inhibit effective job performance of academic librarians at selected universities in North Central Nigeria. Maslow’s hierarchy of needs and task–technology fit theories were the theoretical frameworks underpinning the study. The survey research design was used for the study. The study population consisted of 135 academic librarians and heads of library at seven university libraries. The total enumeration method was then adopted to select academic librarians. Sampling was purposive and enumerative as all members of the population were used for the study. A total of 128 copies of a questionnaire were administered across the seven university libraries. Out of this total, 103 copies were duly completed and returned for quantitative analysis, giving a response rate of 81 per cent. In addition, the census method was used. Copies of the survey questionnaire were used mainly to collect quantitative data from the academic librarians, and interviews were used to collect qualitative data from the university librarians (heads of library). The findings from the study revealed that 90 per cent of the respondents noted that there are hindrances to their job performance.